Improving Prospective Mathematics Teachers’ Writing Skills in Drafting Research Proposals Through the Think, Talk, Write (TTW) Learning Model - Eni Titikusumawati; Baskoro Adi Prayitno (Institut Agama Islam Negeri Imam Bonjol Padang, 2022)
This research was to improve the prospective mathematics teachers’ writing skills in one of the universities in Indonesia. This was classroom-action research to improve students’ skills in writing research proposals. The quantitative and qualitative methods were used. Final year students were selected as the subjects. Observation sheets, questionnaires, interviews, anecdotal notes, and student final manuscripts were used as the instruments. The data were analyzed quantitatively to see improvements between cycles and learning completion. Data was also analyzed qualitatively to describe the improvements due to the TTW model after the data reduction and triangulation. The results showed that there were improvements to students’ writing skills by using the TTW model. Cycle #1 completion was 45.45%, Cycle #2 was 69.7%, and Cycle #3 was 81.82%. Students’ skills were improved because TTW provided exercises for thinking skills. TTW also improving speech skills by training students to speak in front of class forums, and improving writing skills by training the students to compile research proposals and providing opportunities to consult with teachers.